ETIKA MEDIA SOSIAL DALAM PERSPEKTIF HADIS: Aplikasi Desain Penelitian Tematik Hadis - Maryamah; Muhammad Alif; Salim Rosyadi (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study seeks to identify and analyze the ethical principles of social media from the perspective of hadith. Using a thematic approach (maudhu'i) to hadiths related to communication, oral ethics, enjoining good and forbidding evil, and conveying information, the methodology used is a qualitative study based on library research. The main conclusions indicate that the hadiths of the Prophet encompass the following principles: honesty, speaking with caution, refraining from spreading slander, and the importance of verification (tabayyun). These principles can serve as a guide for creating a moral, responsible, and moderate digital culture in the lives of contemporary Muslims. These principles are also highly relevant as a foundation for social media ethics. The revolution in human communication has occurred due to the development of information technology, particularly through social media. In addition to making information more easily and quickly accessible, social media has transformed into a platform for the spread of hate speech, defamation, fake news, and other immoral practices that contradict Islamic principles. In this regard, the moral and ethical teachings contained in Islamic teachings, derived from the hadith of the Prophet Muhammad (peace be upon him), are relevant for guiding individuals toward dignified and healthy online interactions. They also reflect the role of social media in developing Islamic digital literacy.